Predicting Public Trust in Science: The Role of Basic Orientations Toward Science, Perceived Trustworthiness of Scientists, and Experiences With Science - Wintterlin, Florian; Hendriks, Friederike; Mede, Niels G.; Bromme, Rainer; Metag, Julia; Schäfer, Mike S. (Frontiers in Communication, 2022)
Scientists (and science as a whole) provide evidence and advice for societal problem solving and collective decision-making. For this advice to be heard, the public must be willing to trust science, where “trust” means that one can confidently expect science to provide reliable knowledge and evidence, even if one's understanding of science is bounded. According to the sociological and psychological literature, citizens’ basic attitudes toward, experiences with, and perceived trustworthiness of the trustee serve as antecedents of trust. From this, we developed a model for the public’s trust in science, and we tested this model in a nationally representative survey in Switzerland (N = 1,050). The analysis reveals that trust in science was best predicted by positivistic attitudes toward science (β = .33) and to a lesser extent by trustworthiness assessments of scientists (β = .24). Experiences with science did not predict trust in science (β = .07). These results suggest that stable basic attitudes toward science and its role in society are grounds on which trust in science can be built. Experiences with science did not predict trust in science.